Laparoscopic Adrenal Gland Surgery in Times of COVID – Is a Safety-Interval Before Surgery After COVID-Infection Still Mandatory? - Lang, Lina; Schirren, Malte; Wirth, Ulrich; Hofmann-Kiefer, Klaus; Kroiss, Matthias; Werner, Jens; Zimmermann, Petra (Experimental and Clinical Endocrinology & Diabetes, 2024)
Background Due to a multicenter study early in the coronavirus disease (COVID)-pandemic that revealed an increased risk for postoperative mortality, thromboembolic and pulmonary complications in case of surgery shortly after a COVID infection, current recommendations for planning elective surgeries suggest postponing surgery for at least 7 weeks after COVID infection. However, virus variants have evolved throughout the pandemic, leading to less severe symptoms. Besides, laparoscopic adrenal gland surgery itself is a safe procedure with low morbidity rates. Therefore, this study aimed to compare the perioperative course of patients undergoing laparoscopic adrenalectomy shortly after a COVID-19 infection with those who had not had a recent SARS-CoV-2 infection in 2022.Patients, Material, and Methods All patients who underwent laparoscopic adrenalectomy at the Department for General, Visceral and Transplantation Surgery at Ludwig-Maximilian University between January and December 2022 were included.Results There was no event of thromboembolic or pulmonary complications in the study population. Duration of surgery did not differ between the two groups; neither did the need for postoperative ICU-admittance nor the duration of ICU-stay. Intraoperative FiO2 did not differ, nor did the SpO2 or the number of different catecholamines. There was a slight trend towards higher noradrenaline dosage among patients after COVID-19 infection. Previous COVID infection did not lead to prolonged hospital stays.Conclusion The results demonstrate that in case of well-standardized surgical procedures, with a limited surgical trauma and the possibility for patients to be mobilized early, surgery shortly after a mild COVID infection seems safe and reasonable.
Keywords: adrenal gland surgery; SARSCoV-2-infection; perioperative outcome